The elusive nature of mucormycosis in an immunocompetent host and the role of a dermatology consult - Dylan J. Badin; Catherine Baker; Brian J. Simmons; Shaofeng Yan; Kathryn A. Zug (Clinical Case Reports, 2019)
Key Clinical Message Mucormycosis infection in the immunocompetent host typically occurs in the setting of trauma and presents a diagnostic challenge. The earliest signs of infection are often cutaneous, but can easily be misinterpreted, which can be a fatal mistake. Dermatology has tools to help recognize these infections and initiate earlier therapy.